Polymer Change Approach for Formulation of Aceclofenac Sustained Release Tablet - MALVIYA, NAGESHWAR; SONARTIYA, SUNITA; PATIDAR, SUNITA; SETHIYA, PRANAY; JOSHI, APURVA; MUDGAL, KAJAL; KHATEEK, DISKHA (Journal of Biomedical and Pharmaceutical Research, 2022)
Aceclofenac is a non-steroidal anti-inflammatory drug (NSAID) analog of diclofenac. Aceclofenac works by inhibiting the action of cyclooxygenase (COX) that is involved in the production of prostaglandins (PG) which is accountable for pain, swelling, inflammation and fever. Modified drug delivery system has been used to improve the drug absorption and bioavailability. Sustained release tablet of Aceclofenac has been prepared with the help of different polymers for better results. In this review article, a new approach has been studied for the formulation of sustained release tablet of Aceclofenac by changing the polymers. Different polymers has been studied for the formulation of Aceclofenac SR tablet which shows better absorption and improved bioavailability. This suggests that marketed formulations of Aceclofenac tablet should be prepared and evaluated with this new approach for better results.